2019
DOI: 10.1002/hep4.1396
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐32 Contributes to Human Nonalcoholic Fatty Liver Disease and Insulin Resistance

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a metabolic disorder due to increased accumulation of fat in the liver and in many cases to enhanced inflammation. Although the contribution of inflammation in the pathogenesis of NAFLD is well established, the cytokines that are involved and how they influence liver transformation are still poorly characterized. In addition, with other modifiers, inflammation influences NAFLD progression to liver cirrhosis and hepatocellular carcinoma, demonstrating the need to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 53 publications
2
43
0
Order By: Relevance
“…UBD encodes for ubiquitin D, which is implicated in the formation of Mallory-Denk bodies during steatohepatitis and is also upregulated in liver cancer 44. Supporting our findings, while this manuscript was under revision, Dali-Youcef et al also reported upregulation of hepatic expression of IL32 and UBD in obese individuals with NASH, providing initial evidence consistent with a role of IL32 in inducing hepatic insulin resistance 45…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…UBD encodes for ubiquitin D, which is implicated in the formation of Mallory-Denk bodies during steatohepatitis and is also upregulated in liver cancer 44. Supporting our findings, while this manuscript was under revision, Dali-Youcef et al also reported upregulation of hepatic expression of IL32 and UBD in obese individuals with NASH, providing initial evidence consistent with a role of IL32 in inducing hepatic insulin resistance 45…”
Section: Discussionsupporting
confidence: 83%
“… 44 Supporting our findings, while this manuscript was under revision, Dali-Youcef et al also reported upregulation of hepatic expression of IL32 and UBD in obese individuals with NASH, providing initial evidence consistent with a role of IL32 in inducing hepatic insulin resistance. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes Il-32 is increased in nonalcoholic fatty liver disease and steatohepatitis 84 Correlated with liver steatosis, inflammation, and fibrosis in hepatitis C virus infected patients 84,125 Gastric tissue Found in cytoplasm of gastric epithelial cells 68 Elevated in gastritis and positively correlated with gastric inflammation and Helicobacter pylori 68,69 Helicobacter pylori 68,69 Pancreatic islets Coxsackie B virus 13 Gastric cancer/ cell lines Up-regulated compared to healthy controls 128 Associated with poorer prognosis, metastasis and clinicopathologic features 129 Correlated with tumor progression and poor prognosis, increased migration, and invasive properties 106 Induced by Helicobacter pylori, activates pro-inflammatory signaling and transcription 68 Helicobacter pylori 68,69…”
Section: Pgn 16mentioning
confidence: 99%
“…83 Another study looking at NAFLD patients found a similar up-regulation of IL-32 and also noted an inhibition of insulin signaling in primary human hepatocytes pretreated with IL-32, suggesting a role for IL-32 in insulin resistance. 84 The exact role of IL-32 in relation to metabolic disorders is unclear, and it is possible that IL-32 initially is up-regulated as a protective mechanism against accumulation of fatty acids. However, over longer time periods, the pro-inflammatory effects of IL-32 and its potential effects on insulin resistance could play an important role in the pathogenesis of metabolic disorders.…”
Section: Leishmania Infectionsmentioning
confidence: 99%
“…The overexpression of Igfbp2 has been shown to reverse diabetes and steatosis in obese mice [37]. Downregulation of Igfbp2 was reported to be the maker of NAFLD [38]. As a symptom of metabolic disorders, hepatic lipid accumulation is strongly associated with insulin resistance [39].…”
Section: Zro 2 -Nps Induced Lipid Accumulation and Apoptosis Excessimentioning
confidence: 99%